Effect of Problem Based Learning Model on Ability Imelda Medan Private Middle School Student Problem Solving - Putri Zamsari; Asmin (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to determine the effect of the problem-based learning model on the problem-solving abilities of Imelda Medan Private Middle School students. This research was conducted at Imelda Medan Private Middle School in the odd semester of the 2022/2023 school year. The subjects in this study were class VIII students of Imelda Medan Private Middle School. The research sample was taken using the cluster random sampling method, with a post-test only control group research design. The hypothesis test shows the results of tcount 5.459 > ​​ttable 2.074, it can be concluded that the level of problem solving abilities of students in the experimental class is better than that of control class students. To see how much influence is carried out using the effect size which shows the value of d = 1.608 so that it is known that the magnitude of the influence of the problem based learning model on students' problem solving abilities is 94.5%. This can prove the hypothesis that the problem-solving abilities of students who are taught by the problem-based learning model are better than the problem-solving abilities of students who are taught by ordinary learning.